Duration of maternal mental health-related outcomes after an infant’s death: A retrospective matched-cohort study using linkable administrative data - Wall-Wieler, Elizabeth; Roos, Leslie; Bolton, James (International Journal of Population Data Science, 2018)
Introduction Mothers have increased mental illness such as anxiety and depression after the death of a child. Objectives and Approach The mental health of all mothers who experience the death of an infant (< 1 years old) in Manitoba, Canada between April 1, 1999, and March 31, 2011 (n = 534) is examined in the four years leading up to, and the four years following, the death of their child to determine how long increased levels of mental-health realted outcomes remain elevated after the death of an infant. Mental health-related outcomes of these mothers are compared with a matched (3:1) cohort of mothers who did not experience the death of a child (n = 1,602). Results Compared with mothers who did not experience the death of a child, mothers experiencing this event had higher rates of anxiety diagnoses and psychotropic prescriptions starting 6 months before the death. Elevated rates of anxiety continued for the first year and elevated rates of psychotropic prescriptions continued for six months after the death of the child. Mothers who experienced the death of a child had higher rates of depression diagnoses in the year after the death. Relative rates (RR) of depression (RR = 4.94), anxiety (RR = 2.21), and psychotropic medication use (RR = 3.18) were highest in the six months after the child’s death. Conclusion/Implications Elevated rates of depression, anxiety, and psychotropic medication use after the death of a child end within one year of the child’s death.